1996
DOI: 10.1002/eji.1830260625
|View full text |Cite
|
Sign up to set email alerts
|

T cell recognition of Tn‐glycosylated peptide antigens

Abstract: The mouse hemoglobin-derived decapeptide Hb (67-76), VITAFNEGLK, which binds well to Ek and is non-immunogenic in CBA/J mice, was O-glycosylated with the tumor-associated carbohydrate Tn (alpha-D-N-acetylgalactosamine, or alpha-D-GalNAc). Each of the ten positions in the peptide was substituted with serine or threonine having the Tn antigen attached. The complete set of Tn-glycosylated peptides were then studied for binding to Ek and for immunogenicity in CBA/J mice. All of those glycopeptides which had the Tn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…This model has some parallel with immunogenicity of the platelet blood group HPA-1a, where the responsive Th repertoire is thought to be enhanced because the amino acid substitution in the antithetical HPA-1b sequence directly prevents binding to the restricting MHC molecule and thus induction of self-tolerance. 26,36 However, although addition of carbohydrate to key residues may reduce the ability of peptides to bind restricting MHC molecules, 37,38 in the case of k sequences, the glycosylation site N 191 is not predicted to be such an anchor. We, therefore, consider it more likely that the N-glycosylation interferes with T-cell recognition of the MHC-peptide complex.…”
Section: Discussionmentioning
confidence: 99%
“…This model has some parallel with immunogenicity of the platelet blood group HPA-1a, where the responsive Th repertoire is thought to be enhanced because the amino acid substitution in the antithetical HPA-1b sequence directly prevents binding to the restricting MHC molecule and thus induction of self-tolerance. 26,36 However, although addition of carbohydrate to key residues may reduce the ability of peptides to bind restricting MHC molecules, 37,38 in the case of k sequences, the glycosylation site N 191 is not predicted to be such an anchor. We, therefore, consider it more likely that the N-glycosylation interferes with T-cell recognition of the MHC-peptide complex.…”
Section: Discussionmentioning
confidence: 99%
“…In the APC it has been shown that carbohydrates can play a role in protein assembly and folding, can provide protease protection and can also determine the orientation and location of the binding sites of the proteins [15][16][17]. In RA and CIA, cartilage proteins (including CII) typically undergo degradation by matrix metalloproteinases, leading to the generation of peptides that can bind to MHC II and then cause T cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…Although these vaccines elicit antibody responses, it would also be advantageous if T cells could be directed to tumor-associated carbohydrate antigens (2)(3)(4)(5)(6). Posttranslationally modified cytosolic peptides carrying O-␤-linked N-acetylglucosamine (GlcNAc) can be presented by class I MHC molecules to the immune system that activate CTLs, as resolved by wheat germ agglutinin (WGA)-binding profiles reacting with GlcNAc containing glycopeptides in the MHC Class I binding site (7,8).…”
Section: Introductionmentioning
confidence: 99%